Two Analytical Techniques for Fractional Differential Equations with Harmonic Terms via the Riemann–Liouville Definition - Ragwa S. E. Alatwi; Abdulrahman F. Aljohani; Abdelhalim Ebaid; Hind K. Al-Jeaid (Mathematics, 2022)
This paper considers a class of non-homogeneous fractional systems with harmonic terms by means of the Riemann–Liouville definition. Two different approaches are applied to obtain the dual solution of the studied class. The first approach uses the Laplace transform (LT) and the solution is given in terms of the Mittag-Leffler functions. The second approach avoids the LT and expresses the solution in terms of exponential and periodic functions which is analytic in the whole domain. The current methods determine the solution directly and efficiently. The results are applicable for other problems of higher order.